The intrinsic structure and interrelations of tea culture constructed from tea-related toponym texts: Evidence from China - Yiru Xu; Rong Wang; Hongqi Wu (PLoS ONE, 2026)
Tea culture is an important part of the regional culture and intangible cultural heritage that is valued and favored worldwide. The connotations of tea culture are mapped and precipitated in toponyms, which significantly influence the naming and renaming of said toponyms. However, rigorous research integrating tea culture and geographical naming systems is still premature, with a robust analytical framework yet to be established. This study explores China’s Hunan Province as the main research area, adopts the grounded theory method to explore the connotations of tea culture in tea-related toponym texts, and examines in depth the structure of tea culture as well as its internal relationships. The study notes that the more profound the tea culture, the more tea-related toponyms. Evidently, tea culture and toponyms are related. The results show that, on the one hand, the structure of tea culture can be deconstructed into six elements, namely tea tree, tea custom, tea industry, tea activity, tea polity, and tea shape. The structural inheritance and development of tea culture are the result of the interaction of various elements. On the other hand, tea culture’s internal structure comprises two interactive unit systems. From the overall-unit perspective, the natural environment and cultural atmosphere interact. The tea tree is the core of the natural environment, while the cultural atmosphere is jointly created by tea custom, tea industry, tea activity, tea polity, and tea shape. From the perspective of internal structural units, the six elements of tea culture’s structure interact to form an “effect-feedback” mutual influence pattern. This study systematically elucidates the structure of tea culture and interactions between its constituent elements. Such an analysis is crucial for a deeper understanding of local tea culture’s structural inheritance mechanisms. This study provides theoretical support and practical guidance for the development of tea-related industries.